Human Luteinized Granulosa Cells—A Cellular Model for the Human Corpus Luteum - Bagnjuk, Konstantin; Mayerhofer, Artur (Frontiers in Endocrinology, 2019)
In the ovary, the corpus luteum (CL) forms a temporal structure. Luteinized mural granulosa cells (GCs), which stem from the ruptured follicle, are the main cells of the CL. They can be isolated from follicular fluid of woman undergoing in vitro fertilization. In culture, human GCs are viable for several days and produce progesterone, yet eventually steroid production stops and GCs with increasing time in culture undergo changes reminiscent of the ones observed during the demise of the CL in vivo. This short review summarizes the general use of human GCs as a model for the primate CL and some of the data from our lab, which indicate that viability, functionality, survival and death of GCs can be regulated by local signal molecules (e.g., oxytocin and PEDF) and the extracellular matrix (e.g., via the proteoglycan decorin). We further summarize studies, which identified autophagocytotic events in human GCs linked to the activation of an ion channel. More recent studies identified a form of regulated cell death, namely necroptosis. This form of cell death may, in addition to apoptosis, contribute to the demise of the human CL. We believe that human GCs are a unique window into the human CL. Studies employing these cells may lead to the identification of molecular events and novel targets, which may allow to interfere with CL functions.